Association Between the Seat Belt Sign and Intra‐abdominal Injuries in Children With Blunt Torso Trauma in Motor Vehicle Collisions. (November 2014) - Borgialli, Dominic A.; Ellison, Angela M.; Ehrlich, Peter; Bonsu, Bema; Menaker, Jay; Wisner, David H.; Atabaki, Shireen; Olsen, Cody S.; Sokolove, Peter E.; Lillis, Kathy; Kuppermann, Nathan; Holmes, James F.; et al.
Abstract Objectives The objective was to determine the association between the abdominal seat belt sign and intra‐abdominal injuries (IAIs) in children presenting to emergency departments with blunt torso trauma after motor vehicle collisions (MVCs). Methods This was a planned subgroup analysis of prospective data from a multicenter cohort study of children with blunt torso trauma after MVCs. Patient history and physical examination findings were documented before abdominal computed tomography (CT) or laparotomy. Seat belt sign was defined as a continuous area of erythema, ecchymosis, or abrasion across the abdomen secondary to a seat belt restraint. The relative risk (RR) of IAI with 95% confidence intervals (CIs) was calculated for children with seat belt signs compared to those without. The risk of IAI in those patients with seat belt sign who were without abdominal pain or tenderness, and with Glasgow Coma Scale (GCS) scores of 14 or 15, was also calculated. Results A total of 3, 740 children with seat belt sign documentation after blunt torso trauma in MVCs were enrolled; 585 (16%) had seat belt signs. Among the 1, 864 children undergoing definitive abdominal testing (CT, laparotomy/laparoscopy, or autopsy), IAIs were more common in patients with seat belt signs than those without (19% vs. 12%; RR = 1.6, 95% CI = 1.3 to 2.1). This difference was primarily due to a greater risk of gastrointestinal injuries (hollow viscous or associated mesentery) in those with seat belt signs (11% vs. 1%; RR = 9.4, 95% CI = 5.4 to 16.4). IAI was diagnosed in 11 of 194 patients (5.7%; 95% CI = 2.9% to 9.9%) with seat belt signs who did not have initial complaints of abdominal pain or tenderness and had GCS scores of 14 or 15. Conclusions Patients with seat belt signs after MVCs are at greater risk of IAI than those without seat belt signs, predominately due to gastrointestinal injuries. Although IAIs are less common in alert patients with seat belt signs who do not have initial complaints of abdominal pain or tenderness, the risk of IAI is sufficient that additional evaluation such as observation, laboratory studies, and potentially abdominal CT scanning is generally necessary.